Clinical case of gender dysphoria in a patient with a procedural disease - A. I. Kovalev; O. A. Bukhanovskaya; A. V. Dyachenko; M. A. Temirova (Медицинский вестник Юга России, 2022)
The article presents the current state of the problem of patients with gender dysphoria. The heterogeneity of clinical groups within which this phenomenon occurs is shown. It is indicated that a thorough clinical and paraclinical examination is necessary for the correct choice of further therapeutic and diagnostic tactics. As an example, a clinical case of a 14-year-old patient who applied to a medical center due to dissatisfaction with her sexual identity, as well as problems of increasing social maladaptation, in the form of self-harm and suicidal behavior is given. During the examination, the patient was diagnosed with schizotypal disorder in which optional symptoms developed in the form of gender dysphoria due to the presence of symptoms of dysmorphic mania in combination with affective manifestations. Correctly chosen therapeutic tactics led to stabilization of the patient's condition and complete relief of symptoms of gender dysphoria.